Effect of bone marrow stromal cells in combination with biomaterials in early phases of distraction osteogenesis: An experimental study in a rabbit femur model. Issue 11 (November 2018) - Montes-Medina, Laura; Hernández-Fernández, Alberto; Gutiérrez-Rivera, Araika; Ripalda-Cemboráin, Purificación; Bitarte, Nerea; Pérez-López, Virginia; Granero-Moltó, Froilán; Prosper, Felipe; Izeta, Ander
Graphical abstract: Highlights: BMSC injection improves bone formation in a newly developed model of distraction osteogenesis in rabbit femur. Osteogenic BMSCs promoted the maturity of distracted callus and decreased fibrosis. Animals injected with non-osteogenic BMSCs performed identical or worse than controls in all parameters analyzed. Injection of osteogenic BMSCs with fibrin and ground cortical bone modified the ossification mode to intramembranous type. We propose that testing of osteogenic differentiation capacities of the BMSC cultures is required prior to clinical use. Abstract: Acceleration of the consolidation of the distracted bone is a relevant medical need. As a platform to improve in vivo bone engineering, we developed a novel distraction osteogenesis (DO) model in a rabbit large bone (femur) and tested if the application of cultured bone marrow stromal cells (BMSCs) immediately after the osteotomy promotes the formation of bone. This report consists of two components, an animal study to evaluate the quality of the regenerate following different treatments and an in vitro study to evaluate osteogenic potential of BMSC cultures. To illuminate the mechanism of action of injected cells, we tested stem cell cultures enriched in osteogenic-BMSCs (O-BMSCs) as compared with cultures enriched in non-osteogenic BMSCs (NO-BMSCs). Finally, we included a group of animals treated with biomaterials (fibrin and ground cortical bone) in addition to cells. Injection of O-BMSCs promoted the maturity of distracted callus and decreased fibrosis. When combined with biomaterials, O-BMSCs modified the ossification pattern from endochondral to intramembranous type. The use of NO-BMSCs not only did not increase the maturity but also increased porosity of the bone. These preclinical results indicate that the BMSC cultures must be tested in vitro prior to clinical use, since a number of factors may influence their outcome in bone formation. We hypothesize that the use of osteogenic BMSCs and biomaterials could be clinically beneficial to shorten the consolidation period of the distraction and the total period of bone lengthening.